Peran Corporate Social Responsibility dalam Meningkatkan Keberlanjutan Usaha Mcdonald’s Pancing Medan - Hartono, Angeline; Celine Nobel Tunggal; Stephanie Alysio; Steven, Steven; Irvan Rolyesh Situmorang (IPM2KPE, 2026)
This study aims to analyze the role of Corporate Social Responsibility (CSR) in increasing the desire to try McDonald's Pancing Medan through a participatory approach involving the surrounding community. The research method used was community service with the Asset-Based Community Development (ABCD) and Participatory Action Research (PAR) approaches, implemented through observation, interviews, CSR program planning, activity implementation, and periodic evaluation. The results show that CSR implementation can increase community participation, reduce plastic waste, and increase the income of local MSMEs through training programs, mentoring, and environmental campaigns. Furthermore, the formation of a solid mitigation group strengthens the relationship between the company and the community, creating shared value and enhancing the company's positive image. In conclusion, the participatory and sustainable implementation of CSR plays a crucial role in supporting the sustainability of the company's business, from a social, environmental, and economic perspective. Keywords: Corporate Social Responsibility, Business Sustainability, Environment